Comparative Study of Early Versus Delayed Laparoscopic Cholecystectomy for Acute Cholecystitis: A Single-Centre Experience - Adhikari, Dinesh; Bhattarai, Amit; Adhikari, Bigyan; Kafle, Aakash; Paudel, Dipesh (Journal of Nobel Medical College, 2026)
Background: Symptomatic gallstone disease, particularly acute calculous cholecystitis, is a leading surgical emergency globally. While laparoscopic cholecystectomy is the definitive treatment, consensus on the optimal timing of surgery remains debated, with traditional delayed management being challenged by evidence favouring early intervention within 72 hours. This study aimed to compare outcomes between early and delayed laparoscopic cholecystectomy in a tertiary care setting in Nepal. Materials and Methods: This prospective comparative study was conducted from April to July 2025. One hundred twelve patients were stratified into an Early Group (surgery ≤72 hours from symptom onset, n=56) and a Delayed Group (surgery after 6 to 12 weeks of symptom onset, n=56). Outcomes measured included operative time, intraoperative difficulties, hospital stay, and complications. Results: Early laparoscopic cholecystectomy was associated with a significantly shorter hospital stay (2.0 vs. 2.3 days, p = 0.02) compared to delayed surgery, with no significant differences in operative time, conversion rate, or postoperative complications between the two groups. No major morbidity or mortality occurred in either group. Conclusion: Early laparoscopic cholecystectomy for acute cholecystitis is safe and yields outcomes comparable to delayed surgery with respect to operative difficulty, conversion rate, and postoperative complications. Its significant advantage lies in reducing hospital stay, supporting its adoption as the preferred treatment approach for suitable patients.